(untitled) (Biological Sciences - PJSIR, 1995)
Biochemical changesin rice stored at"10°, 25°and45°C for 6 monthswerestudied.The changes in pH,titratable acidity and loss in solids of the rice stored at 25° and45°C were significant. Amylase activity of the samples showed a decrease during storage. Asignificantdecrease inwater solubleamylosealongwithanincreaseininsoluble amylose contents was observed during storage of rice at 25° and 45°C. However, total amylose contents of rice remained un- changed during 6 months storage.